Horrid Henry Robs the Bank - Simon, Francesca; Illustrated by Ross, Tony (New York Source Books Jabber Wocky Pulishers, 2013)
Four brand new stories in which Horrid Henry helps himself to all the money he needs to win his favorite board game, comes up with another spectacular money-making scheme for launching a newspaper with all the school gossip, vows vengeance on Perfect Peter when Peter steals his birthday party theme and has his own Pirate Party and gets his revenge by taking over as head teacher when Peter plays school with his goody-goody friends.
Keywords: Horrid Henry (Fictitious character) -- Children's stories, English